Analisis Berpikir Intuitif Siswa dalam Menyelesaikan Masalah Persentase - Andi Harpeni Dewantara; Sari Saraswati (Didaktika : Jurnal Kependidikan, 2021)
Intuitive thinking is a non-analytic cognitive process, in which the emergence of ideas is spontaneous and emerges suddenly. In learning mathematics, intuitive thinking is sometimes needed as a thinking bridge in an effort to solve a problem. This research is a descriptive qualitative study that aims to analyze how students involve their intuitive thinking skills in solving percentage problems and to assess their difficulties encountered in that process. The collecting data was employed by giving a test with three problem solving questions followed by a depth interview. This study involved 25 students of grade 5 SD IBA Palembang with heterogeeous cognitive performance; low, middle and high. The data then analyzed qualitatively. The results reveal that intuitive thinking, basically, could support students to deal with the percentage problems. All the prior knowledge and experiences lead them to develop their ability to solve the given contextual problems in varied ways, including the use of percentage bar and percentage line-like model.Keywords: Intuitive thinking, percentage, mathematical problem solving